2022
DOI: 10.1007/s10811-022-02763-6
|View full text |Cite
|
Sign up to set email alerts
|

Asexual propagation of Asparagopsis armata gametophytes: fragmentation, regrowth and attachment mechanisms for sea-based cultivation

Abstract: The red algal genus Asparagopsis produces secondary metabolites that when fed to ruminants reduce methane production by up to 98%. However, cultivation methods for Asparagopsis are nascent and fundamental information on reproduction, which is essential for large-scale cultivation, is lacking. In this study we examined asexual propagation in Asparagopsis armata, the regrowth of fragments and mechanisms of attachment to assess the potential for fragments to be used in sea-based cultivation. Asparagopsis armata g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
5
2
Order By: Relevance
“…These findings differ to those found for A. armata in New Zealand and Tasmania where regrowth from single hooks was not possible (Bonin and Hawkes, 1987;Wright et al, 2022), but are in close agreement to those found in France where regrowth occurred (Codomier et al, 1979;Haslin and Pellegrini, 2001). The lack of regrowth in New Zealand and South Australia has been suggested to be attributed to seasonal effects or the existence of genetically different strains (Wright et al, 2022). In fact, there are genetic evidences of different clades of A. armata clearly linked to its geographic distribution (Dijoux et al, 2014;Preuss et al, 2022) and differences among these strains have been previously reported for other phenological responses (e.g.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…These findings differ to those found for A. armata in New Zealand and Tasmania where regrowth from single hooks was not possible (Bonin and Hawkes, 1987;Wright et al, 2022), but are in close agreement to those found in France where regrowth occurred (Codomier et al, 1979;Haslin and Pellegrini, 2001). The lack of regrowth in New Zealand and South Australia has been suggested to be attributed to seasonal effects or the existence of genetically different strains (Wright et al, 2022). In fact, there are genetic evidences of different clades of A. armata clearly linked to its geographic distribution (Dijoux et al, 2014;Preuss et al, 2022) and differences among these strains have been previously reported for other phenological responses (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…Study findings showed how the development of new fronds from single hooks collected in northern Spain (1-3cm length) is possible. These findings differ to those found for A. armata in New Zealand and Tasmania where regrowth from single hooks was not possible (Bonin and Hawkes, 1987;Wright et al, 2022), but are in close agreement to those found in France where regrowth occurred (Codomier et al, 1979;Haslin and Pellegrini, 2001). The lack of regrowth in New Zealand and South Australia has been suggested to be attributed to seasonal effects or the existence of genetically different strains (Wright et al, 2022).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Gametophytes of Asparagopsis have been cultivated on longlines in wave‐sheltered waters, 89,91 while tetrasporophytes have been cultivated on land in small tanks (~110 L) and using finfish effluent a source of nutrients and carbon dioxide to enhance production 88,93 . A. armata gametophytes can be asexually propagated and fragmented fronds that contain barbs are attached to substrate for new tissue to grow 94 . A. taxiformis lacks barbs, therefore, seeding of tetraspores produced by cultured tetrasprophytes onto suitable substrate in a nursery is proposed as an alternative strategy for growth of gametophytes at sea in this species 82 .…”
Section: Priority Seaweeds For Cultivation and Knowledge Gapsmentioning
confidence: 99%
“…88,93 A. armata gametophytes can be asexually propagated and fragmented fronds that contain barbs are attached to substrate for new tissue to grow. 94 A. taxiformis lacks barbs, therefore, seeding of tetraspores produced by cultured tetrasprophytes onto suitable substrate in a nursery is proposed as an alternative strategy for growth of gametophytes at sea in this species. 82 Based on current published knowledge, the life cycle has not yet been closed (from gametophyte to gametophyte), and so biomass production remains reliant on harvest of wild stock and/or fragmentation of the various life stages.…”
Section: Industry Cultivation and Knowledge Gapsmentioning
confidence: 99%